2022
DOI: 10.15578/squalen.692
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative Responses of Chlorella vulgaris Under Different Growth Phases

Abstract: Chlorella vulqaris is a unicellular microorganism that offers health benefits due to its concentrated antioxidant production. This microalga has received huge attention due to its natural antioxidative property as an alternative antioxidant source because of its rapid growth, easy and flexible culture. Research to date only focuses on the growth and antioxidant production in a selected growth phase, especially exponential and stationary phases; however, so far, limited reports on the production of antioxidants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
(60 reference statements)
0
2
0
Order By: Relevance
“…The polyphenolic contents in microalgae, particularly C. vulgaris , are known for their antioxidant qualities due to the high concentration of polyphenolic compounds (Li et al , 2007; Wang et al , 2023). These compounds play a crucial role in reducing the quantity of oxidative stress molecules by efficiently scavenging reactive oxygen species (ROS) and converting them into less harmful substances (Yusuf and Athirah, 2022). Studies have shown that C. vulgaris exhibits significant enzymatic and nonenzymatic antioxidant activities throughout its growth phases, making it a promising source of antioxidants for various industries (Sedjati et al , 2023).…”
Section: Radical Scavengingmentioning
confidence: 99%
“…The polyphenolic contents in microalgae, particularly C. vulgaris , are known for their antioxidant qualities due to the high concentration of polyphenolic compounds (Li et al , 2007; Wang et al , 2023). These compounds play a crucial role in reducing the quantity of oxidative stress molecules by efficiently scavenging reactive oxygen species (ROS) and converting them into less harmful substances (Yusuf and Athirah, 2022). Studies have shown that C. vulgaris exhibits significant enzymatic and nonenzymatic antioxidant activities throughout its growth phases, making it a promising source of antioxidants for various industries (Sedjati et al , 2023).…”
Section: Radical Scavengingmentioning
confidence: 99%
“…Vitamin C can be obtained from different microalgae such as Chlorella whose content can reach 266.67 μg/g Fwt [ 148 ], Nannochloris , and Dunaliella [ 152 ]. Vitamin C exerts its antioxidant effects by activating the NRF2 transcription factor as well as by acting as a direct ROS scavenger [ 149 ].…”
Section: Microalgal Molecules With Antioxidant Actionmentioning
confidence: 99%